DIFFICULTIES IN TEACHING PHRASEOLOGICAL UNITS TO ESL/EFL STUDENTS - Abduxalikova Ruxshona Raxmatulla qizi,; Muxsumova Zebo Sherzod qizi,; To‘xtayeva Laylo Otaxon qizi,; To‘xtaeva Ruxshona Shuhratjon qizi, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This paper explores the major challenges encountered in teaching phraseological units (idioms) to ESL/EFL learners. Phraseological expressions are an essential part of natural communication, yet they remain one of the most difficult aspects of language learning due to their figurative meanings and cultural specificity. The study focuses on learner’s difficulties, instructional gaps, and effective teaching strategies. It highlights that students often struggle with comprehension, contextual usage, and cultural interpretation of idioms. Additionally, the research emphasizes the importance of interactive teaching methods in overcoming these barriers and improving communicative competence.